The Faithfulness of the Main Character Michael Hosea in Redeeming Love Film by D.J. Caruso Character Analysis - Lambaiyang, Jumliyati (Journal Corner of Education, Linguistics, and Literature, 2025)
In doing this research, the researcher take place in Manado city and it be done nearly in three months to complete this research. The researcher obtains the data for this research be taken on the film and the internet. The researcher uses a qualitative method in this research. In qualitative research, the researcher is the primary instrument for gathering and analyzing the data. This research uses the instrument in conducting the research. the research does not need a questionnaire. The research directly observed the data from the film and internet.  Redeeming Love is a story that depicts the struggle of a woman who is unable to escape her past and find redemption until she meets Michael Hosea, a man who shows her unconditional love and faithfulness. Every scene in the movie is there for a purpose.  There is nothing gratuitous in any scene.